2007
DOI: 10.1016/j.vetmic.2006.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia ruminantium variants which do not cause heartwater found in South Africa

Abstract: In 1994 a batch of apparently healthy goats was selected for intended export to the USA from a heartwater-free and vector tick-free region of South Africa. The animals were tested serologically for heartwater, using either or both an IFA and an ELISA test, and 52% were found to be serologically positive. A PCR assay based on Ehrlichia ruminantium 16S gene sequences gave positive results for 54% of the animals, suggesting that apparently non-pathogenic E. ruminantium variants existed in this heartwater-free are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…Similar findings were also reported in a recent study (Allsopp et al 2007), in which the pCS20 PCR failed to give amplicons from ticks from which E. ruminantium 16S sequences were obtained; this finding was attributed to the presence of polymorphisms in one or both of the pCS20 nested amplification primer target sites thus preventing effective hybridization and chain extension. The same authors (Allsopp et al, 2007) reported the detection of pCS20 and 16S sequences in animals and non-Amblyomma tick species in a heartwater-free area in South Africa (Northern Cape) and suggested the presence of a non-pathogenic variant of E. ruminantium in this area.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar findings were also reported in a recent study (Allsopp et al 2007), in which the pCS20 PCR failed to give amplicons from ticks from which E. ruminantium 16S sequences were obtained; this finding was attributed to the presence of polymorphisms in one or both of the pCS20 nested amplification primer target sites thus preventing effective hybridization and chain extension. The same authors (Allsopp et al, 2007) reported the detection of pCS20 and 16S sequences in animals and non-Amblyomma tick species in a heartwater-free area in South Africa (Northern Cape) and suggested the presence of a non-pathogenic variant of E. ruminantium in this area.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the map1 gene of E. ruminantium has been reported to exhibit a high degree of sequence polymorphism (Reddy et al 1996;Allsopp et al 2001), whereas the lack of amplification by pCS20 primers (AB128/AB129 primers, Mahan et al 1992) could be attributed to the design of these primers in a comparatively less conserved region of the pCS20 sequence (Van Heerden et al 2004). Similar findings were also reported in a recent study (Allsopp et al 2007), in which the pCS20 PCR failed to give amplicons from ticks from which E. ruminantium 16S sequences were obtained; this finding was attributed to the presence of polymorphisms in one or both of the pCS20 nested amplification primer target sites thus preventing effective hybridization and chain extension. The same authors (Allsopp et al, 2007) reported the detection of pCS20 and 16S sequences in animals and non-Amblyomma tick species in a heartwater-free area in South Africa (Northern Cape) and suggested the presence of a non-pathogenic variant of E. ruminantium in this area.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These findings suggest that several strains of E. ruminantium were introduced with A. variegatum in the 19th century . As single animals reportedly can be infected with multiple E. ruminantium genotypes (Allsopp et al 2007) and be healthy carriers for months (Andrew and Norval 1989), the concomitant importation of different pathogenic genotypes is unsurprising.…”
Section: Introductionmentioning
confidence: 99%
“…There are scanty reports on the ability of this species to transmit diseases in both humans and animal. However, it is a known vector agent of the protozoan Babesia bigemina, Crimean-Congo hemorrhagic fever virus (CCHFV), and Ehrlichia ruminantium [55][56][57]. Mediannikov et al [54] has reported on the ability of R. evertsi evertsi to transmit rickettsial agents in ticks that were collected in Senegal.…”
Section: Discussionmentioning
confidence: 99%